An experimental investigation of the aerodynamic flows created by lorries travelling in a long platoon. Issue 193 (October 2019) - Robertson, Francis H.; Bourriez, Frederick; He, Mingzhe; Soper, David; Baker, Chris; Hemida, Hassan; Sterling, Mark
Abstract: The concept of autonomous road vehicles has recently gained a great deal of technical respectability. Expected advantages over normal driver-controlled vehicles are through increased safety, reliability and fuel efficiency. This paper presents a novel experimental study enabling for the first time a full understanding of the aerodynamic flow development of a long vehicle platoon. Moving model experiments were carried out at the University of Birmingham Transient Aerodynamic Investigation (TRAIN) rig facility on a 1/20th scale eight lorry platoon with three constant vehicle spacings. Slipstream velocity and pressures, as well as simultaneous on-board vehicle surface pressure measurements were made. Results indicated a highly turbulent boundary layer development, with slipstream pulse peaks near the front of each lorry; similar to previous findings on flows around container freight trains. The drag coefficient of an isolated lorry was in agreement with previous studies. There are substantial reductions in aerodynamic drag for the non-leading platoon vehicles. Drag results plateaued towards a constant value within the platoon. Vehicle spacing affected drag values, with decreases of 57% observed for the closest spacing of half a vehicle length, demonstrating the aerodynamic benefits of platooning. Highlights: The boundary layer is highly turbulent with pulse peaks near the front of each lorry. Aerodynamic drag plateaus towards a constant value within a long lorry platoon. Aerodynamic drag is reduced substantially for the non-leading lorries. For an inter-vehicle spacing of half the lorry length, the drag is reduced by 57%.